Between icon and picture: painting icons in Russia between the 18th and 20th centuries - Walczak Dorota (Studia Humanitatis, 2022)
The article is devoted to the phenomenon of the so-called “painting icon” in Russia between the 18th and 20th centuries. “Painting icon” is a type of icon painting that uses the artistic means characteristic of painting, primarily light and shade modelling and portraiture. The author analyses specific icons belonging to this direction. A connection is established between the emergence of the “painting icon” and social and cultural changes in Russia that influenced the understanding of the theology of the icon.